2016
DOI: 10.1080/17441692.2016.1180702
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and social support among ball-attending African American men who have sex with men and transgender women are associated with HIV-related outcomes

Abstract: The House Ball Community (HBC) is an understudied network of African American men who have sex with men and transgender women, who join family-like houses that compete in elaborate balls in cities across the United States. From 2011 to 2012, we surveyed 274 recent attendees of balls in the San Francisco Bay Area, focusing on social networks, social support, and HIV-related behaviours. Participants with a high percentage of alters who were supportive of HIV testing were significantly more likely to have tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…The use of social networks emerged as a key theme in navigation strategies. Alternative family structures and strong community supports are frequent characteristics of queer communities, 36 , 37 and particularly characteristic of the “punk/queer” community in NOLA, which is anecdotally associated with a wide national network of social connection. The data showed more use of social networks to access CAM for those within this community, suggesting that GM individuals outside this smaller subset may not have access to this resource.…”
Section: Discussionmentioning
confidence: 99%
“…The use of social networks emerged as a key theme in navigation strategies. Alternative family structures and strong community supports are frequent characteristics of queer communities, 36 , 37 and particularly characteristic of the “punk/queer” community in NOLA, which is anecdotally associated with a wide national network of social connection. The data showed more use of social networks to access CAM for those within this community, suggesting that GM individuals outside this smaller subset may not have access to this resource.…”
Section: Discussionmentioning
confidence: 99%
“…With this information, programs and interventions can be designed that build on existing human and social capital in this community in order to prevent the spread of HIV. As systems of social support and identity-affirmation, houses and families are considered sources of resilience that support and protect their members from the stresses that YBMSM often endure (Arnold, Sterrett-Hong, Jonas, & Pollack, 2016; Kubicek et al, 2013; Wong et al, 2014). For many, the stability a house or family provides cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…In one study it was found that greater density amongst members of a social network was associated with lower rates of serodiscordant condomless intercourse (SDCI) with a non-primary partner, an effect that did not differ by race/ethnicity [19]. Another study found no connection between social network density and sexual risk behavior [20]. ("racial disparity" OR "racial disparities" OR health status disparities OR healthcare disparities OR African americans OR latinos OR minorities OR ethnic OR ethnicity OR black OR "racial inequity" OR minority) AND (hiv infections OR "hiv transmission" OR acquired immunodeficiency syndrome OR "hiv seropositivity" OR sexually transmitted diseases OR STI OR gonorrhea OR syphilis OR chlamydia OR HPV OR "sexual risk behavior" OR "condomless sex" OR "condomless anal intercourse" OR "unprotected sex" OR "sex drug use" OR "unprotected intercourse") AND The studies that focused on size and density of sexual networks were not conclusive.…”
Section: Size and Densitymentioning
confidence: 99%
“…emotional, instrumental, informational, appraisal) [24]. Two studies included measures of "HIV-related" social support [15,20]. Most studies Full-text articles assessed for eligibility (n = 75 )…”
Section: Social Supportmentioning
confidence: 99%